(3GdbjGOI GdEOGQjI aj GdeDSSGJ GdCefjI (B/s - (3GdSGMhQj, fGUQs ((3YeGf, GdCQOf (B:s (3OGQ CeLO ddfTQ hGdJhRjY,s, 2017)
(3jJfGhd cJGH (B((3GdbjGOI GdEOGQjI aj GdeDSSGJ GdCefjI(B) (3GdPj bGe HJCHag fGUQ LeYI GdSGMhQj aj MhGdj (B(233) (3UaMI ef GdbWY GdeJhSW ehVhY (B((3GdbjGOI GdEOGQjI aj GdeDSSGJ GdCefjI(B) (3eSJYQVG GdehVhYGJ GdJGdjI (B: (3GdebOeI, GdaUd GdChd (B: (3eGgjI GdCef hLgGR GdTQWI, GdaUd GdKGfj (B: (3GdbjGOI hYdGbJgG HGdeDSSGJ GdCefjI, GdaUd GdKGdK (B: (3eJWdHGJ hebheGJ GdGSJQGJjLjI aj GdeDSSGJ GdCefjI, GdaUd GdQGHY (B: (3GdLhOI GdTGedI hGdYed GdCefj, GdaUd GdNGeS (B: (3GdYdGbGJ GdYGeI hGdEYdGe aj GdeDSSGJ GdCefjI, GdeQGLY(B. s
(3HHdjhLQGajI (B: (3UaMI (B225-232.s
Keywords: (3GdCef GdOGNdjs -- (3LeYjGJ, EdN(B.s -- (3EOGQIs; (3GdTQWI GdEOGQjIs